Attractors for the Brusselator in R^N (Journal of Partial Differential Equations, 2007)
We consider the reaction-diffusion system, a model of a certain chemical morphogenetic process and named Brusselator. For the Cauchy problem of this system with nondecaying initial data, the existence and uniqueness of the global solution is established. Moreover, it is proved that this system possesses a global attractor A in the corresponding phase space.